Automation tool for taxonomic classification in the family Geminiviridae - Gomes, Ruither Arthur Loch (Universidade Federal de Viçosa, 2018)
Pathogenic microorganisms have the potential to cause serious problems for humankind. Their precise taxonomic classification is an important step for understanding and combating the diseases caused by them. Several technologies were created to make it easier to classify microorganisms, and with the emergence of high-throughput sequencing technologies this process has been hugely accelerated. However, this led to another problem, because extremely large volumes of genetic sequence information are generated, making the bioinformatic analysis of sequences a time-consuming process. In the case of viruses classified in the family Geminiviridae, this problem is compounded by the large amount of new sequences that are deposited in public databases. Geminiviruses are responsible for large losses of production in economically important crops worldwide, which makes them the focus of much research leading to the constant discovery of new viruses. Although there are several ways of performing the taxonomic classification of microorganisms, the use of the percentage of identity obtained from the alignment between individuals has been increasingly applied. In the case of viruses with small genomes, the use of percent identities obtained from pairwise alignments has been applied for decades, so that several algorithms have already been created to accomplish this goal. However, none of the algorithms developed until today carries out the classification of the virus, leaving to the researcher the work of deciding the taxonomic classification, one virus at a time. Here we present a tool that will carry out the classification of viruses in the Geminiviridae. This tool is capable of acquiring the sequences as they are added to public databases or receiving the sequences given by the user. It then filters the added sequences to eliminate those already classified and parses the remaining sequences based on their percentage of pairwise identity with classified viruses . It also updates the values of taxonomic demarcation thresholds used to classify species and strains. Using this tool, it was possible to analyze all viruses added to public databases from January 2017 until July 2018. A total of 27 new species were identified. We also suggest revised demarcation thresholds for the genera Becurtovirus, Capulavirus, Curtovirus, Grablovirus and Mastrevirus.

Os microrganismos patogênicos são a causa de diversos problemas para a humanidade. Sua classificação é um importante passo para o entendimento e combate às doenças por eles causadas. Diversas tecnologias foram criadas para facilitar a classificação, e com o surgimento das tecnologias de sequenciamento de alto rendimento, esse trabalho foi imensamente acelerado. Entretanto isso gerou outro problema, pois volumes extremamente grandes de informação de sequências genéticas passaram a ser gerados, tornando a análise das sequências um processo que demanda muito tempo. No caso da família Geminiviridae, esse problema é somado à grande quantidade de novas sequências que são depositadas periodicamente nos bancos de dados públicos. Esses vírus são responsáveis por grandes perdas na produção de diversas de culturas de grande importância econômica em todo o mundo, o que leva à constante descoberta de novos geminivírus. Apesar de existirem diversas formas de classificar os microrganismos, a utilização da porcentagem de identidade obtida do alinhamento entre os indivíduos vem sendo cada dia mais aplicada. No caso de vírus com genoma pequeno, a utilização da identidade obtida de alinhamentos par-a-par já é aplicada há décadas, de modo que diversos algoritmos já foram criados para realizar essa tarefa. Entretanto nenhum dos algoritmos desenvolvidos até o presente realizam a classificação taxonômica dos vírus, deixando para o pesquisador o trabalho de realizar a classificação, vírus por vírus. Neste trabalho apresenta-se uma ferramenta que realiza a classificação de vírus da família Geminiviridae. A ferramenta é capaz de adquirir as sequências à medida que são adicionadas nos bancos de dados públicos, ou de recebê- las diretamente do usuário. Em seguida, filtra as sequencias adicionadas a fim de eliminar aquelas correspondentes a vírus já classificados, e analisa as restantes com base nas porcentagens de identidade obtidas do pareamento com os vírus já classificados. A ferramenta também atualiza os valores de limites de demarcação taxonômica utilizados para classificar esses vírus aos níveis de espécie e estirpe. Utilizando essa ferramenta foi possível analisar todos os vírus adicionados nos bancos de dados desde janeiro de 2017 até julho de 2018. Um total de 27 novas espécies foram identificadas. Sugere-se também atualizações nos limites de demarcação de espécies e estirpes para os gêneros Becurtovirus, Capulavirus, Curtovirus, Grablovirus e Mastrevirus.
Ferramenta de automatização para classificação taxonômica da família Geminiviridae
Keywords: Begomovírus - Identificação; Micro-organismos patogênicos; Vírus - Classificação; Bioinformática; Fitopatologia